45 anos de PED uma análise da produção de teses e dissertações do programa de Pós-Graduação em Educação: Psicologia da Educação da PUC-SP entre 1996 e 2014 - Tozzato, Noiza Rodrigues Borges (2016)
The current research’s objective is to characterize and analyze the production of thesis and dissertations of the Programa de Estudos Pós-Graduados em Educação: Psicologia da Educação – PED, between 1996 and 2014, continuing a job started in1999 by Moroz et al. The main proposal of this research arose from the realization of the importance of registering the history of PED – which in 2014 completed 45 years of existence. Three from the eight variables analyzed by the group of researchers coordinated by Moroz (1999) were selected to execute this essay: Thematic Cut, Theoretical Cut and Context. The choice of these variables was based on the belief that they would provide enough data to understand the focus and the course that PED has taken over the years: which context is prioritized, which topics are most discussed and which theoretical lines provide the basis for discussion. All the jobs summaries produced by PED within the selected period were found and accessed consulting the Virtual PUC SP SAPIENTIA Library. Using the same criteria as Moroz, spreadsheets composed by tables were produced with numbers referring to the quantity of thesis and dissertations produced by PED within the researched period; all data were grouped within a five-year period. We analyzed 611 productions between thesis and dissertations; this number represents almost twice the amount of analyzed jobs by Moroz and his collaborators. It is notable that within 45 years of its history, PED had a total of 933 doctoral thesis and master dissertations advocated. Through the information regarding the Thematic Cut variable, it was possible to observe a huge thematic dispersion. Generally, the thesis and dissertation production from PED presents very heterogeneous themes. The Referential Theoretical Cut variable enabled the identification of a predominance of jobs based in the theoretical framework of Education and Psychology. The Context variable revealed the predominance of the school environment in surveys conducted by PED. 193 from the 611 analyzed jobs did not contain enough information on their abstracts, this number represents 31, 3% of the analyzed abstracts. Conclusion: Comparing to the survey conducted in 1999, we noticed a significant increase in the production of thesis and dissertations. Furthermore, we observed that in the original publication, the authors, facing the huge percentage of abstracts in which the information was insufficient for classification, pointed to the necessity to “the post-graduate programs to guide the student in the preparation of the abstract.” It was possible to notice a decline in the percentage of jobs grouped in the information failure classification, and also new themes appeared within these 45 years of PED’s production, such as: Inclusion, Violence, Public Politics, Arts, Ethics, Justice and Citizenship, Affection and Learning, and the Relation between the school and the scholarship community